2016
DOI: 10.1371/journal.pone.0168095
|View full text |Cite
|
Sign up to set email alerts
|

Cantharidin Induced Oral Squamous Cell Carcinoma Cell Apoptosis via the JNK-Regulated Mitochondria and Endoplasmic Reticulum Stress-Related Signaling Pathways

Abstract: Oral cancer is a subtype of head and neck cancer which represents 2.65% of all human malignancies. Most of oral cancer is histopathologically diagnosed as oral squamous cell carcinoma (OSCC). OSCC is characterized by a high degree of local invasion and a high rate of metastasis to the cervical lymph nodes. How to prevention and treatment of OSCC is important and imperative. Here, we investigated the therapeutic effect and molecular mechanism of cantharidin, an active compound isolated from blister beetles, on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 57 publications
5
34
0
Order By: Relevance
“…Previous studies have reported that CTD efficiently inhibited proliferation and induced apoptosis in various cancer cells, including oral squamous cell carcinoma, renal carcinoma and gastric cancer cells (18)(19)(20). The results of the present study also demonstrated that CTD inhibited A549 cell proliferation and migration, which is consistent with the results of previous studies (18)(19)(20).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies have reported that CTD efficiently inhibited proliferation and induced apoptosis in various cancer cells, including oral squamous cell carcinoma, renal carcinoma and gastric cancer cells (18)(19)(20). The results of the present study also demonstrated that CTD inhibited A549 cell proliferation and migration, which is consistent with the results of previous studies (18)(19)(20).…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study also demonstrated that CTD inhibited A549 cell proliferation and migration, which is consistent with the results of previous studies (18)(19)(20). The combined results of these studies provide evidence that CTD is a promising therapeutic candidate for the treatment of NSCLC.…”
Section: Discussionsupporting
confidence: 92%
“…We found 1 0 missorting and aggregation of GPI-anchored GFP-CD59 in the cytoplasm of HeLa cells upon CTD treatment, which was very similar to that of Gas1-GFP in yeast. Similarly, CTD also induced phosphorylation of p44/42 (yeast Slt2), supporting the previous observations of CTD-mediated activation of different MAPKs (18,21). We also found decreased expression of XBP1 (yeast HAC1) upon CTD treatment which might be via ATF6 signaling that regulates the target gene XBP1 (65).…”
Section: Discussionsupporting
confidence: 91%
“…The inhibition of PP2A causes cell cycle arrest (25,26) and apoptosis (27,28). CTD also impairs different cellular processes such as heat shock response (29), autophagy (22), DNA damage response, and mitogen-activated protein kinase (MAPK) signaling (18,21). One of these studies also demonstrated a PP2A or PP1 independent alteration in heat shock response (29), suggesting the existence of additional molecular targets of CTD (29,30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation